Diffuse Parenchymal Lung Disease 2017
DOI: 10.1183/1393003.congress-2017.pa1519
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of serum biomarkers in patients with sarcoidosis: Can visfatin be a new biomarker for sarcoidosis?

Abstract: Objective: Sarcoidosis is a chronic systemic inflammatory disease which can affect multiple organ systems. The role of biomarkers in the diagnosis and prognosis of sarcoidosis is increasing. Interest in the role of adipose tissue mediated inflammation in the pathogenesis of the inflammatory diseases has increased in recent years. Visfatin is a proinflammatory adipocytokine which has been studied for several inflammatory diseases such as diabetes mellitus, obesity and metabolic syndrome. Our aim is to assess se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(35 reference statements)
0
0
1
Order By: Relevance
“…With the exception of IL-8, each biomarker in the sarcoidosis panel (eNAMPT, IL-6, ANG-2 IL-1RA, and HBEGF) accurately discriminated between healthy controls and sarcoidosis subjects, with an optimal threshold > 74%. Our plasma eNAMPT results strongly contrast with a previous report indicating no difference between sarcoidosis and healthy controls (38), possibly reflecting differences in studied cohorts as well as biomarker analytic methodologies (commercial ELISA vs. MSD). Each panel biomarker exhibited unique biomarker properties with IL-1RA and ANG-2 exhibiting the most diagnostic accuracy in distinguishing sarcoidosis from healthy subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…With the exception of IL-8, each biomarker in the sarcoidosis panel (eNAMPT, IL-6, ANG-2 IL-1RA, and HBEGF) accurately discriminated between healthy controls and sarcoidosis subjects, with an optimal threshold > 74%. Our plasma eNAMPT results strongly contrast with a previous report indicating no difference between sarcoidosis and healthy controls (38), possibly reflecting differences in studied cohorts as well as biomarker analytic methodologies (commercial ELISA vs. MSD). Each panel biomarker exhibited unique biomarker properties with IL-1RA and ANG-2 exhibiting the most diagnostic accuracy in distinguishing sarcoidosis from healthy subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Acute phase reactants, such as ESR and CRP, have been used regularly in clinical practice in the workup of skin infections and even showed good results in predicting the severity of such conditions [14]. Also, ESR and CRP were found to be elevated in sarcoidosis patients [15]; similarly, this was noted in our patient. In the literature, case studies reported an overlap between subcutaneous sarcoidosis and skin infections.…”
Section: Discussionsupporting
confidence: 79%